Promoting global education in science and engineering: An experience in Indonesian high schools. (March 2019) - Triawan, F; Biddinika, M K; Hanaoka, S; Takahashi, F; Aziz, M
Abstract: Japan has initiated higher education reform in which internationalization is one of the challenges as a way to improve excellence in research and competitiveness within Asia and the world. In becoming the "Asian Gateway" to the rest of the world, Japan also invites students from Asian countries to pursue higher education in Japan. However, language problem is often considered as one of the barriers faced by international students – not only from Asian countries – in Japan, especially for undergraduate program since the program is mostly held in Japanese language. The Global Scientists and Engineers Program (GSEP) is the international bachelor of engineering degree program in Tokyo Institute of Technology (Tokyo Tech). It does not require any Japanese language ability since the whole program would be taught in English. This paper presents the experience of promotional activities of the program in Indonesia in order to identify the challenges, to document the method, and to outline some recommendations for improvement. The promotion was held by presentation in front of 13 (thirteen) high schools in Jakarta and nearby. After the promotional presentation, participants were also requested to express their interest in applying the program as well as their perceived usefulness of the presentation.